The Effect of a Project-Based Learning (PjBL) Model Incorporating Balinese Intrument on the Creativity of Fifth-Grade Elementary School Students in the SBdP Curriculum - I Gusti Agus Kelana Putra Pratama; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2026)
Arts and Culture learning at the elementary school level often demonstrates limited development of student creativity due to instructional practices that are less varied and insufficiently student-centered. This condition necessitates the application of learning models that are capable of fostering higher-order creative thinking through meaningful learning experiences. The main objective of this study was to analyze and evaluate the effect of Project-Based Learning assisted by Balinese gamelan on students’ creativity by emphasizing higher-order cognitive processes at levels C4–C6. A quantitative approach was employed using a quasi-experimental design with a non-equivalent control group. The research subjects consisted of 39 fifth-grade students, comprising 20 students in the experimental group and 19 students in the control group. Data were collected using creativity assessment instruments administered through pre-test and post-test procedures, which had met validity and reliability criteria. Data analysis included normalized gain score analysis, normality testing, homogeneity testing, and hypothesis testing using pooled variance t-test. The results showed that the experimental group achieved a higher mean normalized gain score (0.464, moderate category) compared to the control group (0.295, low category), with a calculated t-value of 3.814 exceeding the critical value of 2.026 at a 5% significance level. The conclusion, indicate a significant difference in student creativity between the two groups. The implication suggests that Project-Based Learning assisted by Balinese gamelan serves as an effective pedagogical alternative for enhancing creativity in elementary Arts and Culture learning.